2018
DOI: 10.1111/bjd.16713
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitizing antihypertensive drug use and risk of cutaneous squamous cell carcinoma

Abstract: These findings provide moderate support for an increased cSCC risk among individuals treated with photosensitizing ADs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 23 publications
2
44
0
Order By: Relevance
“…Photosensitising thiazide antihypertensives have been recently associated with the risk of cSCC development [67,68], however causality has not been substantiated. A meta-analysis by Gandini et al reported no association between thiazide diuretics and cSCC [69].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Photosensitising thiazide antihypertensives have been recently associated with the risk of cSCC development [67,68], however causality has not been substantiated. A meta-analysis by Gandini et al reported no association between thiazide diuretics and cSCC [69].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…The study by Su et al . indirectly supports these data, as findings for ever‐use of photosensitizing antihypertensive drugs were driven by combination diuretics, which include hydrochlorothiazide …”
mentioning
confidence: 52%
“…In this issue of the BJD , Su et al . provide evidence linking photosensitizing antihypertensive drugs to increased risk of cSCC . The study included a cohort of 28 357 non‐Hispanic white adults with hypertension who participated in a research programme at Kaiser Permanente Northern California and were followed up for biopsy‐verified in situ /invasive cSCC .…”
mentioning
confidence: 99%
See 2 more Smart Citations